2021
DOI: 10.1111/eip.13193
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the COVID‐19 lockdown on adolescents with an eating disorder and identifying factors predicting disordered eating behaviour

Abstract: Aim To evaluate the impact of the COVID‐19 lockdown on adolescents with eating disorders (ED) and identify factors predicting ED behaviour. Method This study took place during an age‐stratified lockdown for those under 20 years in Turkey. Participants completed a survey developed to evaluate the effects of the lockdown on ED behaviour, well‐being and quality of life (QoL) and additionally the eating disorder examination questionnaire (EDE‐Q), and scales for depression, anxiety and obsessive‐compulsive behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 25 publications
(33 reference statements)
2
16
0
Order By: Relevance
“…In terms of lockdown measures, there were mixed results with some patients deteriorating and some improving during lockdown. Several studies found worsening symptoms for ED patients during lockdown (Baenas et al, 2020 ; Brown et al, 2021 ; McCombie et al, 2020 ; Monteleone, Marciello, et al, 2021 , Nistico et al, 2021 ; Springall et al, 2021 ) and issues with accessing treatment services during lockdown (Akgül et al, 2021 ; Clark Bryan et al, 2020 ). However, some studies demonstrated that patients did better during lockdown, for example, AN patients showed improvement of ED psychopathology and a progressive weight gain, and BN patients had less binge‐eating episodes during lockdown (Castellini et al 2020 ; Giel et al, 2021 ), while other's found mixed results with some patients deteriorating and some improving during lockdown (Machado et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of lockdown measures, there were mixed results with some patients deteriorating and some improving during lockdown. Several studies found worsening symptoms for ED patients during lockdown (Baenas et al, 2020 ; Brown et al, 2021 ; McCombie et al, 2020 ; Monteleone, Marciello, et al, 2021 , Nistico et al, 2021 ; Springall et al, 2021 ) and issues with accessing treatment services during lockdown (Akgül et al, 2021 ; Clark Bryan et al, 2020 ). However, some studies demonstrated that patients did better during lockdown, for example, AN patients showed improvement of ED psychopathology and a progressive weight gain, and BN patients had less binge‐eating episodes during lockdown (Castellini et al 2020 ; Giel et al, 2021 ), while other's found mixed results with some patients deteriorating and some improving during lockdown (Machado et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Factors that were associated with worse BI and eating outcomes during the pandemic included psychological, individual, social, and ED‐related characteristics. Psychological variables associated with worse outcomes included higher levels of worry, rumination, loneliness, anxiety, depression, stress, psychological distress, and fear of COVID‐19 (e.g., Akgül et al, 2021 ; Chan & Chiu, 2021 ; Frayn et al, 2021 ; Swami, Horne, et al, 2021 ); comorbidity of mental health concerns and childhood trauma (e.g., Castellini et al, 2020 ; Chan & Chiu, 2021 ); insecure attachment, lower self‐directedness, and poor coping strategies (e.g., Baenas et al, 2020 ; Haddad et al, 2020 ); poor emotion regulation (e.g., Félix et al, 2021 ; Flaudias et al, 2020 ; Machado et al, 2020 ); higher levels of uncertainty intolerance (e.g., Scharmer et al, 2020 ); and greater food insecurity (e.g., Christensen, Forbush, et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The second theme identified was an investigation of the perceived impact of the pandemic on eating disorder or mental health symptoms. Twenty‐two studies examined this theme, with 16 studies sampling clinical populations (participant n s = 12–1,021; Akgül et al, 2021 ; Baenas et al, 2020 ; Branley‐Bell & Talbot, 2020 ; Favreau et al, 2021 ; Graell et al, 2020 ; Machado et al, 2020 ; Quittkat et al, 2020 ; Richardson et al, 2020 ; Schlegl, Maier, Meule, & Voderholzer, 2020 ; Schlegl, Meule, Favreau, & Voderholzer, 2020 ; Shaw et al, 2021 ; Spettigue et al, 2021 ; Spigel et al, 2021 ; Termorshuizen et al, 2020 ; Vitagliano et al, 2021 ; Vuillier et al, 2021 ) and six studies sampling non‐clinical populations (participant n s = 90–5,469; Athanasiadis et al, 2021 ; Buckley et al, 2021 ; Coimbra et al, 2021 ; Keel et al, 2020 ; Phillipou et al, 2020 ; Robertson et al, 2021 ). In all cases, the authors developed their own items assessing perceived impacts of COVID‐19.…”
Section: Resultsmentioning
confidence: 99%
“…These findings were observed whether symptom levels were assessed with or without reference to pre‐COVID levels (e.g., Branley‐Bell & Talbot, 2020 ; Phillipou et al, 2020 ), in comparison to pre‐COVID cohorts (e.g., Kim et al, 2021 ; Taquet et al, 2021 ), and were also supported by data from healthcare providers (Colleluori et al, 2021 ). Individuals with an eating disorder also reported broader mental health concerns related to the pandemic (Akgül et al, 2021 ; Quittkat et al, 2020 ), suggesting that COVID‐19 impacts in this population may not be localized to eating disorder psychopathology. Lack of structure and disrupted routines, greater exposure to environmental triggers, and difficulties regulating emotion were highlighted as possible precipitants for symptom deterioration (Termorshuizen et al, 2020 ; Vuillier et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%